2020
DOI: 10.1038/s41416-020-0849-z
|View full text |Cite
|
Sign up to set email alerts
|

Pregnancy-related risk factors for sex cord-stromal tumours and germ cell tumours in parous women: a registry-based study

Abstract: BACKGROUND: Non-epithelial ovarian cancers are divided into sex cord-stromal tumours (SCSTs) and germ cell tumours (GCTs). Whereas parity and other pregnancy-related factors are protective for epithelial ovarian cancer, their associations with SCSTs and GCTs remains unclear. METHODS: Using data from the medical birth registries from Denmark, Finland, Norway and Sweden, we compared all parous women with a diagnosis of SCSTs (n = 420) or GCTs (n = 345) 1970-2013 with up to 10 parous controls (SCSTs n = 4041; GCT… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
7
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
4

Relationship

3
1

Authors

Journals

citations
Cited by 4 publications
(7 citation statements)
references
References 27 publications
(31 reference statements)
0
7
0
Order By: Relevance
“…Although pregnancies seem to have a limited impact on the risk of these rare tumors, 26 we found that parous women diagnosed with GCTs had a clearly better prognosis than nulliparous women. To our knowledge, there are no previous studies on the prognostic impact of parity in nonepithelial ovarian cancer.…”
Section: Discussionmentioning
confidence: 50%
See 3 more Smart Citations
“…Although pregnancies seem to have a limited impact on the risk of these rare tumors, 26 we found that parous women diagnosed with GCTs had a clearly better prognosis than nulliparous women. To our knowledge, there are no previous studies on the prognostic impact of parity in nonepithelial ovarian cancer.…”
Section: Discussionmentioning
confidence: 50%
“…Although pregnancies seem to have a limited impact on the risk of these rare tumors, 26 we found that parous women diagnosed with GCTs had a clearly better prognosis than nulliparous women. Since it is less likely that women are young when diagnosed with a malignancy have had children before their diagnosis, the group of nulliparous women will have a low mean age at diagnosis.…”
Section: Noneepithelial Ovarian Cancermentioning
confidence: 50%
See 2 more Smart Citations
“…Non-epithelial ovarian cancers are divided into sex cord-stromal tumours (SCSTs) and germ cell tumours (GCTs). We investigated the associations of pregnancy characteristics by these subtypes in the Nordic Project (49). Like our findings in epithelial ovarian cancer, the risk of SCSTs, but not GCTs, decreased with older age at first and last birth.…”
Section: Ovarian Cancermentioning
confidence: 70%